Optimasi Charger Controller Pembangkit Listrik Picohidro Kapasitas 250 Watt - Dewi, Rozlinda; Suprapto, Eko; Wahyuni, Kanthi (Universitas Batanghari Jambi, 2024)
PLTMH is one of the renewable energy power plants that is environmentally friendly. Indonesia has considerable hydropower potential that can be developed into Micro / Mini Hydro Power Plants of 19,385 MW spread throughout Indonesia [2]. PicoHidro Power Plant is part of PLTMH with an output power of < 1 kW [1]. The advantages of this plant are generating electricity without being too influenced by seasons and day and night changes, power generation fluctuations are relatively small, the possibility of electricity generation is high, the impact on the environment is very small and the fast response is suitable for peak load conditions and when there is a disturbance in the network. PLPicohidro uses a DC generator that utilizes a power source for battery charging. The battery is used as an inverter voltage source to turn on the AC load. For that, a Charger Controller is needed which is useful for charging the battery. The DC voltage source coming from the generator is stored using a battery and then goes to the inverter to be converted into AC voltage. In this study, automatic charging of two batteries was used or can be called automatic charging. The way this circuit works is when the battery is full, the charger will automatically stop. The voltage indication during the charger process is 11 Volts and stops when the voltage reaches 14 volts. The use of two batteries in the charger process can work alternately, if battery 1 is full then battery 2 will charge automatically, and vice versa.